Crystal structure of poly[(μ3-3, 5-dichloro-2-hydroxy-benzoato-κ4 Cl,O:O′:O″) silver(I)], C7H3AgCl2O3 - Jiang Jin-Ke; Niu Chun-Yan (Zeitschrift für Kristallographie - New Crystal Structures, 2023)
C7H3AgCl2O3, monoclinic, P21/c (no. 14), a = 13.1492(5) Å, b = 3.72760(10) Å, c = 16.5625(6) Å, β = 92.1810(10)°, V = 811.22(5) Å3, Z = 4, R gt(F) = 0.0229, wR ref(F 2) = 0.0492, T = 301(2) K.